The Effectiveness of GTM Plus on Students' English b - Nur Laila Molla (Universitas Pancasakti Tegal, 2014)
Grammar Translation Method (GTM) is one of teaching methods. The writer discovered a new model of GTM, later called GTM Plus. This research will prove whether this method completely effective to students' achievement. Several experiments are taken to two difference classes. The experiments were held at Junior High School 1 Tegal. There were two sample classes consisting of twenty two students for each, one as experimental class and the other as control class. Experimental class was taught with GTM Plus and the other class without. There were pre-test and post-test for both classes. A true experimental research was held. Test and observation conducted, the writer calculated test validity, reliability, difficulty level and discriminating power. The Sample of students was taken randomly. The test is analyzed and calculated using nonparametric statistic. The result proves 21.6% increasing students' achievement. The pre-test mean of control group is 6.11 and 6.72 for post-test while the pre-test mean of experimental group is 7.07 and 8.56 for post-test. Percentage of score improvement is 21.1%. This means that the implementation of Grammar Translation Method GTM) Plus gives positive effect to students' achievement on English reading tests and also speaking ability. The results show that mean of experimental group is higher than of control group. This gives positive effect on the implementation of Grammar Translation Method (GTM) Plus at school widely. Analyzing feedback through questionnaire of experimental group also shows 86% acceptance of this teaching method.